Smart Structures and Materials 1998: Industrial and Commercial Applications of Smart Structures Technologies 1998
DOI: 10.1117/12.310623
|View full text |Cite
|
Sign up to set email alerts
|

Integration of piezoceramic actuators in fiber-reinforced structures for aerospace applications

Abstract: Up to now experimental and theoretical research on active structures for aerospace applications has put the focus mainly on surface bonded actuators. Simultaneously piezoceraniics became the major type of actuating device being investigated for smart structures. In this context various techniques of insulating, bonding and operating these actuators have been developed. However, especially with regard to actuators only a few investigations have dealt with embedding of these components into the load bearing stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2003
2003

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Substrate (steel) d 1 = 1.35 l meas = 105 a E (1) = 220 ν (1) = 0.29 Piezoelectric ceramic (PZT Sonox P53) d 3 = 0.2 L = 20 E (3) x = E (3) y = 66.7 ν (3) xy = 0.358 d (3) 31 = d (2) 32 = −0.287 × 10 by Volkswagen AG (VW) and the German Aerospace Center (DLR). The piezoceramic plates are cut into smaller pieces (area: 20 × 10 mm 2 , thickness: 200 µm) and provide a surface uniformly covered with electrodes to take advantage of the 'd 31 -effect'.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Substrate (steel) d 1 = 1.35 l meas = 105 a E (1) = 220 ν (1) = 0.29 Piezoelectric ceramic (PZT Sonox P53) d 3 = 0.2 L = 20 E (3) x = E (3) y = 66.7 ν (3) xy = 0.358 d (3) 31 = d (2) 32 = −0.287 × 10 by Volkswagen AG (VW) and the German Aerospace Center (DLR). The piezoceramic plates are cut into smaller pieces (area: 20 × 10 mm 2 , thickness: 200 µm) and provide a surface uniformly covered with electrodes to take advantage of the 'd 31 -effect'.…”
Section: Methodsmentioning
confidence: 99%
“…the piezoceramic, is equal to the free piezoelectric strain, γ s, (3) x , at this position, while the substrate has not been able to gain any strain there. The resulting misfit u x between the opposite faces of piezolayer and substrate causes a shear deformation γ (2) xz of the adhesive layer that, on the other hand, induces a shear stress τ adh . The shear stress is responsible for a stress transfer from the piezolayer to the substrate, resulting in a gradual compensation of the misfit with increasing distance from the edge position.…”
Section: The Influence Of Transverse Deformationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since it had already been shown that, depending on the specific configuration, higher efficiency can be obtained by embedding actuators rather than bonding them to a surface [39], the initial design of the CFRP mirror comprised piezoceramic actuators embedded holohedrally into the face-sheets. This initial design for the CFRP mirror gave a total thickness of 54 mm while mass was calculated to be 5.3 kg (18.7 kg m −2 ).…”
Section: Composite Designmentioning
confidence: 99%